SASTRA ANAK, MEDIA PEMBENTUKAN KARAKTER PADA ANAK USIA SEKOLAH DASAR - Ni Putu Eni Astuti; Ida Bagus Putrayasa; I Nyoman Sudiana; Pande Agus Adi Wijaya; Ni Kadek Anggreni (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2024)
More serious concerns should be raised to cope with the degradation of noble values and wisdom behaviors of the children by the parents, teachers, and all educational stakeholders. Character education is one of the solutions to this issue. Building the character of elementary school children can be done through children literature and selecting appropriate reading materials based on their development level. This study aimed at describing the contribution of children literature in character education and selecting the children literature based on the elementary school children development level. It is a descriptive qualitative study in form of library research. Based on the data analysis, it was found that (1) the children literature contributes to the development of individual values reviewed from the aspects of emotion, intellectual, imagination, social, ethics, and religion of the children, as well as the value of education reviewed from aspects of exploration and discovery, language, beauty, multicultural insight, and reading habit; (2) the selection of children literature, must adjust to the development stage of the intelligence, moral, emotion and personalization, as well as language of the children. The appropriate readings for elementary school children in the stage of concrete operational (7-11 years old) are narrative books or story books, such as legend, adventure, or traditional literature, as well as poetical and drama learning